Meningkatkan motivasi belajar siswa melalui layanan bimbingan COVID berbasis ZOZIZZ - Ni Wayan Sri Yasmini (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2021)
The background for this best practice writing is the low learning motivation of grade IX students at SMP Negeri 1 Selemadeg during the Covid-19 pandemic. Students are indifferent to assignments in google classroom, are not disciplined in doing assignments, cheating on friends' assignments and complaining of boredom studying online. The strategy to improve student learning motivation is with the ZOZIZZ-based COVID guidance service, which is an acronym for the Counseling Online guidance service with Zoom and Quizizz-based Video Conferences. The subjects were 23 students of class IX C. The data collection technique uses a learning motivation questionnaire and the results of the evaluation of the implementation of counseling guidance services using google form. Data analysis by comparing the results of the pretest and posttest of the student learning motivation questionnaire. The data processing technique is done descriptively through data reduction, data presentation and conclusion drawing. The steps / strategies in problem solving are service planning, implementation, evaluation and reflection. The result was an increase in the learning motivation of class IX C students after providing ZOZIZZ-based COVID guidance services, namely from the previous 13% low category, 70% medium category and only 17% who had high learning motivation to 90% class IX C students had learning motivation category very high. So it can be concluded that the ZOZIZZ-based COVID guidance service is effective in increasing student learning motivation during the Covid-19 pandemic. Latar belakang penulisan best practice ini adalah mulai rendahnya motivasi belajar siswa kelas IX SMP Negeri 1 Selemadeg di masa pandemi covid-19. Siswa acuh dengan tugas-tugas di google classroom, tidak disiplin dalam mengerjakan tugas, menyontek tugas teman serta mengeluh bosan belajar online. Strategi untuk meningkatkan kembali motivasi belajar siswa adalah dengan layanan bimbingan COVID berbasis ZOZIZZ yaitu akronim dari layanan bimbingan Counseling Online dengan Video Conference berbasis Zoom dan Quizizz. Subjek penelitian adalah siswa kelas IX C yang berjumlah 23 orang. Teknik pengumpulan data menggunakan kuesioner motivasi belajar dan hasil evaluasi pelaksanaan layanan bimbingan konseling dengan google form. Analisis data dengan membandingkan hasil pretest dan post test kuesioner motivasi belajar siswa. Teknik pengolahan data dilakukan secara deskritif melalui reduksi data, penyajian data dan penarikan kesimpulan. Langkah-langkah/strategi dalam penyelesaian masalah adalah perencanaan layanan, pelaksanan, evaluasi dan refleksi. Hasilnya terjadi peningkatan motivasi belajar siswa kelas IXC setelah pemberian layanan bimbingan COVID berbasis ZOZIZZ yaitu dari sebelumnya 13% kategori rendah, 70% kategori sedang dan hanya 17% yang mempunyai motivasi belajar tinggi menjadi 90% siswa kelas IX C memiliki motivasi belajar dengan kategori sangat tinggi. Sehingga dapat disimpulkan bahwa layanan bimbingan COVID berbasis ZOZIZZ efektif meningkatkan motivasi belajar siswa di masa pandemic covid-19.